Effects of quercetin supplementation on exercise induced inflammation and immune cell Changes after exhausting swimming in adolescent girls - Gholami, M.; Ardestani, M. (Asian Journal of Sports Medicine, 2018)
Background: It is suggested that quercetin has anti-inflammatory properties and can improve endurance performance, but study results are contradictory especially in human models. Therefore, the purpose of the present study was to evaluate the effect of quercetin supplementation on TNF-a, lactate and immune cell responses after one session of exhausting swimming.